Research Progress on Preparation Method and Properties of Superhydrophobic Coating of Organic High Polymer - GAO Xiaoyu, ZHANG Heng, LIU Junming, FENG Liming, CHEN Bobo (Cailiao Baohu)
Organic high molecular polymer superhydrophobic coatings have a wide range of material choices， high comprehensive performance，simple preparation methods， and are easy to realize large-scale industrial applications，making them the most likely superhydrophobic materials to be widely promoted.Herein， this paper briefly summarized the design principles of superhydrophobic coatings， reviewed the research progress on several major types of high molecular polymer-based superhydrophobic coatings and their properties both domestically and internationally，and identified the factors limiting their application along with potential solutions.The key to achieving practical applications of organic polymer superhydrophobic coatings lied in ensuring their stability， resistance to environmental damage and excellent comprehensive performance.Thus， gradient design of coatings， high-polymer structure design and optimization of coating application and curing conditions were important pathways to achieve high-performance superhydrophobic coatings.